The New American Reality : Who We Are, How We Got Here, Where We Are Going - Farley, Reynolds, 1938- (Book collections on Project MUSE., 1996)
. The New American Reality also reports the good news about America; our lives are longer and healthier, the elderly are better off than ever before, consumer spending power has increased, and minorities and women have many more opportunities. In this way, The New American Reality challenges those who contend that we are a country in decline. The reality, Farley argues, is far more complex: we are a country in the midst of dramatic change, some of it negative but much of it positive. Understanding that change - and making sense of the information we have about it - will be crucial to the economic and social vitality of America in the twenty-first century.